Untraceable evidence - Stover, Sharee (Love inspired suspense., 2020)
"It's undercover ATF agent Randee Jareau's job to make sure the government's 3-D printed “ghost gun” doesn't fall into the wrong hands. So when someone goes after scientist Ace Steele, she must protect him- before she loses the undetectable weapon and its creator. But with a mole inside Ace's company and everyone a suspect, this assignment could become Randee's last"--$cProvided by publisher.